(untitled) (Academic Journal of Internal Affairs, 2023)
Abstract Aim: The growing social problems in Europe and its immediate environment today, such as illegal migration or the livelihood crisis already threatening the masses in the major Western states as a result of their misguided economic policies, can easily lead to riots, partly due to external causes. In this paper, I aim to provide insights into the applied chemistry underpinning the use of chemical means of coercion, as well as its law enforcement implications. Methodology: In this security environment, we see day after day that mass demonstrations require the use of chemical means of repression to maintain the tactical response capability of the troops of the police forces of the countries concerned, either in self-defence or to suppress unlawful mass demonstrations that often threaten the maintenance of law and order. In this article, the author examines some of the issues relevant to their use. Findings: As our civilisation becomes more and more organised, the organisations responsible for maintaining public safety are also facing increasingly complex law enforcement challenges. In order to meet these challenges, it is essential to ensure that law enforcement agencies have the right head start. The role of organised and effective preventive measures and crime prevention intelligence in the system of tasks that underpins this is gradually increasing, tying up considerable human resources in the organisations concerned. It is therefore essential that, in situations requiring the deployment of police forces with limited availability to maintain law and order, they are able to carry out their tasks with the necessary tactical advantage, using chemical means of restraint and tactical procedures. Value: It is important to note, however, that in the context of other law enforcement agencies or property protection, the ability to use small, limited-range chemical means of coercion is also essential to control aggressive and resistant individuals in the course of their duties. In particular, with regard to the environmental factors affecting the safety of the use of chemical agents used in chemical agents. This will ensure that adequate action is taken in the case of lawful performance of official duties involving the use of the reported means of restraint.